Mineral nutrient analysis of three halophytic grasses under sodic and saline stress conditions - LATA, CHARU; KUMAR, ASHWANI; MANN, ANITA; SONI, SHOBHA; MEENA, B L; RANI, SULEKHA (The Indian Journal of Agricultural Sciences, 2022)
Present study was carried out to assess the effects of soil salinity/sodicity on mineral nutrient status of Urochondra setulosa, Leptochloa fusca and Sporobolus marginatus at ICAR- Central Soil Salinity Research Institute, Karnal, Haryana during 2016–19. Treatments of salinity/sodicity (pH 9.5, pH 10, ECe 30 dS/m, ECe 40 dS/m and ECe 50 dS/m) were created in microplots (2.5 m × 1.5 m × 0.5 m) using saline/sodic water. Na+ and Cl– content (% DW) significantly increased with increasing sodicity/salinity stress condition in all three grass halophytes, whereas K+ content decreased. These grass halophytic species showed relatively less reduction in Ca, Mg and Fe contents up to sodic stress of pH 9.5 and salinity level of ECe 40 dS/m. Zn, Cu and Mn content decreased with increasing stress conditions but higher decrease was observed under sodic stress. The Na+/K+ and Na+/Ca2+ ratio was considered as indicators for measuring salt tolerance in plants. Na+/K+ ratio increased with increasing stress condition in all the three grasses but Leptachloa maintained their Na+/K+ near pH 1.0 under sodic stress condition and also maintained their Na+/Ca2+ below 1.0 up to pH 9.5 and ECe 40 dS/m. Higher sodic stress of pH 10.0 caused significant increase in Na+/Ca2+ in Urochondra and Sporobolus, whereas under highest salinity level, Leptachloa showed highest value for Na+/Ca2+. Changes in the accumulation patterns of nutrient in response to salinity is an important aspect and study showed highest positive correlation between Ca - Mg & Zn and negative between Na - Ca and K.